부재료 첨가에 의한 전통 장류식품 품질 특성 변화에 관한 연구 동향 - 양정아(Jeong-A Yang); 김준영(Jun Young Kim); 신의철(Eui-Cheol Shin); 이영승(Youngseung Lee); 박성수(Sung-Soo Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2023)
본 연구는 전통 대두 발효식품의 부재료 첨가에 따른 품질 특성 변화에 관한 209편의 연구 내역을 장류별로 분류하고 분석하였다. 고추장과 된장의 경우에는 기호성 및 기능성 향상을 위한 다양한 식품소재가 첨가되어 비교적 많은 연구가 진행되었으나, 간장과 청국장에서는 첨가된 부재료의 종류가 한정적이고 품질 특성 연구가 다소 적은 경향으로 장류의 고급화와 다양화를 위해 맛과 풍미를 향상시킬 수 있는 재료를 첨가한 연구가 지속해서 진행되어야 할 것으로 판단된다. 또한 최근 현대인의 나트륨 과잉 섭취에 따른 문제가 대두되고 있는 현실에서 전통 장류는 일상생활에서 다양한 용도로 사용됨으로써 나트륨 주요 섭취원으로 분류되고 있어 이러한 장류의 나트륨 저감화를 위해 부재료 첨가에 따라 염도를 낮추고 저장성을 향상시키는 연구가 이뤄지고 있으나, 청국장에서 염도 관련 연구는 찾아볼 수 없어 장류에서 더욱 다양한 첨가 재료에 따른 연구가 이뤄져야 할 것으로 사료된다. 그리고 부재료 첨가에 따른 고추장, 간장, 된장, 청국장의 품질 특성 연구 논문을 2000년대와 2010년대로 비교한 결과, 전반적으로 시기별로 큰 차이는 보이지 않았다. 이와 관련하여 이후 부재료 첨가 연구가 지속해서 시도된다면 기호 및 상품성을 높인 전통 대두 발효식품이 K-푸드로써 한식의 세계화에도 기여할 수 있을 것으로 판단된다. In the present study, we analyzed and categorized the outcomes of 209 studies on the changes in the quality characteristics of traditional soybean fermented foods caused by the addition of supplementary ingredients. Relatively abundant research has been conducted in this regard on Gochujang (red pepper paste) and Doenjang (soybean paste) which is due to addition of a variety of supplementary ingredient to improve their functionality and meet customer preference. However, research on the addition of ingredients that can enhance the taste and flavor should be conducted continuously to achieve a high-quality and diversity of traditional sauces. This need for ongoing studies is due to earlier limitations existing in the types of supplementary ingredients, which has been the reason for the comparatively lower number of studies performed on the quality characteristics of Ganjang (soy sauce) and Cheonggukjang (fast-fermented bean paste). Although number of investigations are being conducted to reduce the salt content and improve the storability of these sauces by adding supplementary ingredients, no evidence has been published on the content of sodium in Cheonggukjang. In addition, the results of comparative studies on changes in the quality characteristics of Gochujang, Ganjang, Doenjang, and Cheonggukjang by the addition of supplementary ingredients, performed in the 2000s and 2010s, showed no significant differences. Therefore, in the future, continuous research on the supplementation with novel ingredients can improve the commercial values and characteristics of traditional soybean fermented foods, and satisfy more advanced preferences which will contribute to the global popularization and spread of Korean foods. KCI Citation Count: 0